Pitching business presentations with academic discourse / Ena Bhattacharyya - Bhattacharyya, Ena (Akademi Pengajian Bahasa, 2021)
Business communication is the process of sharing information between people within and outside a company. Business Presentations, are one such form of oral workplace communicative event. A Business Presentation occurs when specific business-plans are shared with target-audiences with an underlying purpose to create a decision or move. During such competitive fast paced oral presentations, audience understanding is critical. This understanding is reliant on a presenter’s ability to stress, emphasize, punctuate and signal transitions at right moments of a presentation. The short moment of engagement may either break or close a deal. How then do presenters make themselves easily understood in such highly competitive formal settings? What linguistic devices assists an audience to comprehend a presentation better? This workshop aims to share some insight on the types of useful fillers, idea signallers and discourse markers to navigate audience understanding during a business presentation. It aims to explore the selective use of transitional words, comparatives and qualifiers in the IBC of business pitching for better audience appreciation of a business presentation.